2009
DOI: 10.1159/000252830
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension and Associated Factors among Older Rural Adults: Results from Liaoning Province, China

Abstract: Objective: The objective of the study was to estimate the prevalence of hypertension and associated factors among older rural adults in Liaoning Province, China. Subjects and Methods: The study was conducted in 2004–2006, using a multistage, stratified clustering sampling scheme to select a representative sample. A total of 10,065 adults aged 60 years or older were examined. A survey of blood pressure and associated factors was carried out. All data analyses were conducted using SPSS 11.5 statistical software … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
13
2
4

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 41 publications
9
13
2
4
Order By: Relevance
“…This result was agreed with Oladapo et al [28] who demonstrated a significant relationship between hypertension in university students with a BMI ≥ 25. This result is in line with Pang et al and Sarry El-Din et al [1,29] who had confirmed that obesity and being overweight were the major risk factors in hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…This result was agreed with Oladapo et al [28] who demonstrated a significant relationship between hypertension in university students with a BMI ≥ 25. This result is in line with Pang et al and Sarry El-Din et al [1,29] who had confirmed that obesity and being overweight were the major risk factors in hypertension.…”
Section: Discussionsupporting
confidence: 91%
“…For example, although hypertension was highly prevalent among rural elders, it was found that rates of awareness, treatment and control among rural elders with hypertension were very low. 20,50 Similar to the results of previous studies, 20,50 this study has shown the proportions of those with hypertension who were treated and who received preventive healthcare interventions (e.g., blood pressure tests) were very low. As a basic preventive healthcare service, it is feasible for rural primary healthcare facilities to offer a simple blood pressure test using a medical sphygmomanometer.…”
Section: Discussionsupporting
confidence: 85%
“…In Costa Rica, 65% were hypertensive,7 and 42.4% of women in Accra, Ghana had hypertension 8. In Brazil, self-reported hypertension was 55%,9 in rural China it was 57–64.9%,10 and in another study in China it was 24.2–43.8% 11. In Turkey 71.2–82.2% of subjects had hypertension,12 and in Taiwan 31.1–38.0% 13…”
Section: Introductionmentioning
confidence: 91%
“…Various factors have been found to be associated with hypertension, including socio-demographics (older age, female gender, lower education level, lower household income),13-16 geolocality (urban residence),17 other risk factors or behaviour, including stroke,18 diabetes,19,20 higher body mass index (BMI),5,10,13,14 physical inactivity,16,22,23 insufficient fruit and vegetable intake,13,23-25 smoking and drinking,10,16,22 greater limitations on activities of daily living (ADLs) and instrumental activities of daily living (IADLs),26 higher frequency of doctor visits,4 and less social cohesion 27…”
Section: Introductionmentioning
confidence: 99%